Kateketika Dalam Sejarah Pemikiran Pedagosis Kristen - Jefrie Walean (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2018)
Jefrie Walean,Â Chateketic in history idea Christian Pedagogic. Christian history idea is effort place idea in large of time. Certain to get understanding holistict belived Christian from history idea in the end placed a number of idea which tell as reference doctrine from some church a period history. Christian idea not become property writer of the bible apostles also pater of church but Christian property. Christian idea which concutrently stay in work idea generate way of maner different approach one with otherno wonder that history idea christian write down so munch thinker christian as long as to detected. Clear that,core of Christian ides is human relation with God influence Jesus Christ. Telling about the Christian pedagogic, not realese upon Christian religion didactic.